2022
DOI: 10.3389/fenrg.2021.798037
|View full text |Cite
|
Sign up to set email alerts
|

Primary Frequency Stability Support of a DFIG in Association With Pitch Angle Control

Abstract: For an electric power grid that has large penetration levels of variable renewable energy including wind generation and photovoltaics, the system frequency stability is jeopardized, which is manifest in lowering frequency nadir and settling frequency. This paper suggests an enhanced primary frequency response strategy of a doubly-fed induction generator (DFIG) in association with pitch angle control. The DFIG works in de-loaded operation with a certain reserve power via pitch angle control prior to disturbance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“… [ 100 ] Employing an enhanced primary frequency response (PFR) strategy so as to reduce the pitch angle to slowly feed the active power to the grid system in improving the frequency stability of the system. [ 101 ] Enhancing the capability of frequency regulation by considering the interdependences among the variables including rotor speed, rotor current frequency, and power system frequency by using a novel control strategy applied to maximum energy harvesting. [ 109 ] Based on PMSG technology Optimizing cost and reliability Implementing swap control scheme that facilitates to use the turbine-generator rotor inertia for storing surplus power during grid voltage dips, which ultimately helps to achieve the removal of extra hardware devices; and ensure operation compatibility, lowering size, cost and switching losses of the system.…”
Section: Wecs Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 100 ] Employing an enhanced primary frequency response (PFR) strategy so as to reduce the pitch angle to slowly feed the active power to the grid system in improving the frequency stability of the system. [ 101 ] Enhancing the capability of frequency regulation by considering the interdependences among the variables including rotor speed, rotor current frequency, and power system frequency by using a novel control strategy applied to maximum energy harvesting. [ 109 ] Based on PMSG technology Optimizing cost and reliability Implementing swap control scheme that facilitates to use the turbine-generator rotor inertia for storing surplus power during grid voltage dips, which ultimately helps to achieve the removal of extra hardware devices; and ensure operation compatibility, lowering size, cost and switching losses of the system.…”
Section: Wecs Technologiesmentioning
confidence: 99%
“…In addition, non-superconducting fault current limiter that was based on bridge-type flux coupling method [ 97 ]; external retrofit and internal control techniques [ 98 ]; and dynamic voltage resistor (DVR)-FLC technique [ 99 ] were also proposed to enhance FRT capability based on the modeling of DFIG system components. Moreover, the power reliability with DFIG system operations was reported to be improved based on the implementation of different research modeling strategies including: a novel model reduction margin (MRM) & New England test system (NETS) [ 100 ]; an enhanced primary frequency response (PFR) [ 101 ]; etc. as it can be seen from Table 3 .…”
Section: Wecs Technologiesmentioning
confidence: 99%
“…Most of the existing studies on enhancing the inertia response ability of wind turbines focus on generator rotor control or additional energy storage device to improve the inertia response ability of DFIG. For generator rotor control, there are two methods commonly adopted (Kang et al, 2016;Liu et al, 2017;Altin et al, 2018;Chu et al, 2020;Li et al, 2021b;Xu and Wang, 2021;Si et al, 2022), one is to increase the electromagnetic torque to obtain additional instantaneous power to provide inertia response for system frequency modulation. The essence of this control method is to release the kinetic energy of the blade rotor to compensate for the energy imbalance when the grid frequency fluctuates.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, some studies propose to change its maximum power point tracking (MPPT) curve and obtain power margin through over speed load shedding, which can avoid the second drop of the power grid. In literature (Si et al, 2022), it is suggested an enhanced primary frequency response strategy of a doubly-fed induction generator in association with pitch angle control. The DFIG works in de-loaded operation with a certain reserve power via pitch angle control prior to disturbances for frequency regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Wind turbines (WTs) generally adopt the maximum power point tracking (MPPT) control method, which has no reserve capacity to meet the requirements of frequency regulation (Chen et al, 2023; Dreidy et al, 2017). In order to involve WFs in frequency regulation, the current research mainly focuses on virtual inertial control (Li et al, 2022; Morren et al, 2006) and de-loaded power control (Amaro Pinazo et al, 2022; Ramtharan et al, 2007; Si et al, 2022). Morren et al (2006) proposed a virtual control inertial method by utilizing the rotor kinetic energy (KE) of WTs.…”
Section: Introductionmentioning
confidence: 99%